Pengaruh Kualitas Produk dan Harga Terhadap Kepuasan Konsumen Pada Produk Vacuum Cleaner PT Hyla Abadi di Jakarta - Haura Salsabila; Purwatiningsih, Purwatiningsih; Ratih Setyo Rini (Institut Teknologi dan Bisnis (ITB) Semarang, 2024)
Researchers took the object of research at PT Hyla Abadi, due to a decrease in customer satisfaction which was thought to be due to the influence of product quality and price. Research used is a quantitative approach. The type of research used in this research is descriptive quantitative. In accordance with the research objectivesThe population and samples used were 80 company customers and the sampling used was saturated sampling. used for validity and reliability tests were 30 customers at the same company. Based on the results of the T test, the Sig value of the effect of product quality on customer satisfaction is 0.074 <0.05. It can be concluded that there is no effect of product quality on customer satisfaction. Based on the results of the T test, the Sig value of the effect of price on customer satisfaction is 0.000 <0.05, it can be concluded that there is an effect of price on customer satisfaction. Based on the results of the F test, the significance value of the simultaneous effect of product quality and price variables on customer satisfaction is 0.000 <0.05, so the simultaneous test is accepted, which means that there is a simultaneous effect of product quality and price on customer satisfaction. So it can be concluded partially that the product quality variable has no significant effect on the customer satisfaction variable, but the price variable has a significant effect on customer satisfaction.